Tolerance to deformation and flux pinning in superconducting amorphous molybdenum nitride thin films grown on flexible polyimide - Castellini Grand, P.; Lee, Yeonkyu; Yun, Jinyoung; Kim, Jeehoon; Bengió, Silvina; Sirena, Martin; Haberkorn, Nestor Fabian (Elsevier Science SA, 2023)
Fil: Castellini Grand, P.. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina